The Relationship Between the Quality of Work Life and Organizational Similarity and their Impact on Job Performance: An Analytical Study of the Opinions of Faculty Members in the Faculties of Chermo University - حمد على, مظفر; عمر عبدالله, عباس (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The study aims to analysis the relationship of quality of work life concluded its five dimensions: (salary and bonuses, work environment conditions “health and safety”, job security, job growth and participation in management) to the organizational identification, and knowing the impact of this relationship in job performance. General Framework that adapted by the study is to identifying the study problem through raising several questions, that focused on the nature of the relationship, impact, and the contracts between the study's independent variables representing (quality of work life and organizational identification) and dependent variable (job performance), they subjected to several tests and a questionnaire form used to get the data. The study depended on descriptive analytical method, to describing dimensions of the study variables as well as the study society representing Charmo University Colleges in Chamchamal City, subsequently distributing (123) questionnaire form on the responders (faculty members), (102) valid form were obtained for analysis, and it had been examined the relationship, impact, and variance by applying the statistical methods through SPSS version 22. The research reached a set of conclusions, the most important of which are: There are correlations between independent variables and their impact on the dependent variable at the macro and micro level